The Structural-Pragmatic-Situational Approach in Policy Determination for Optimizing E-Learning in UIN Raden Mas Said Surakarta - Imam Makruf; Muhammad Zaenuri; Anisatul Barokah (Ta'dib: Jurnal Pendidikan Islam, 2022)
The covid-19 pandemic that unexpectedly brought the education world almost stopped due to the ban on face-to-face learning. This research aims to find a suitable policy determination model to optimize e-learning in Islamic universities. This research uses a qualitative approach that combines interviewing, documentation, and focused group discussion in data collection and validation. This research has focused on UIN Raden Mas Said Surakarta, Indonesia, with key respondents being university leaders. Faculty leaders, postgraduates, institutions, units, e-learning managers, and admin staff are informants. The data validation use triangulation and data analysis with interactive models. The study provided findings that the process of policy determination applied is top-down by involving all elements of the leadership democratically. The policies-decision is applied using a structural-pragmatic-situational (SPS) approach. The contribution of this study is an SPS approach can overcome emergencies quickly and appropriately in policy-making.